2020
DOI: 10.3390/jcm9030761
|View full text |Cite
|
Sign up to set email alerts
|

Primary Open Angle Glaucoma and Vascular Risk Factors: A Review of Population Based Studies from 1990 to 2019

Abstract: Glaucoma is one of the leading causes of blindness worldwide, and as the proportion of those over age 40 increases, so will the prevalence of glaucoma. The pathogenesis of primary open angle glaucoma (POAG) is unclear and multiple ocular risk factors have been proposed, including intraocular pressure, ocular perfusion pressure, ocular blood flow, myopia, central corneal thickness, and optic disc hemorrhages. The purpose of this review was to analyze the association between systemic vascular risk factors (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 100 publications
(191 reference statements)
3
85
0
9
Order By: Relevance
“…The vascular theory is based on evidence of either primary (vasospastic syndrome) or secondary vascular dysregulation found in some glaucomatous patients. The chronic impairment of ONH blood flow, which may result from an imbalance in the ocular blood flow auto-regulation and oxidative stress (vasospastic syndrome) or from systemic levels of vasoconstrictive peptides (i.e., endothelin-1), seems to be responsible for ischaemia-reperfusion nerve injury [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vascular theory is based on evidence of either primary (vasospastic syndrome) or secondary vascular dysregulation found in some glaucomatous patients. The chronic impairment of ONH blood flow, which may result from an imbalance in the ocular blood flow auto-regulation and oxidative stress (vasospastic syndrome) or from systemic levels of vasoconstrictive peptides (i.e., endothelin-1), seems to be responsible for ischaemia-reperfusion nerve injury [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic factors, such as systemic hypertension, type 2 diabetes mellitus, and lipid dysregulation may also increase glaucoma risks. Moreover, age, smoking, family history, and genetic factors could also be risk factors [ 33 ]. Although glaucoma may occur at any age, a relationship was found between open-angle glaucoma and increasing age due to other age-related diseases.…”
Section: Therapeutic Potential Of Curcumin In Ophthalmologymentioning
confidence: 99%
“…15 Three systematic reviews examined the associations between diabetes and glaucoma. [7][8][9] Pooled analysis from those studies reported different OR 1.37, (95% CI=0.72-2.02), OR=1.36, (95% CI=1.25-1.50) and OR=1.48, (95% CI=1.29-1.71). Alhough the results seem close and suggest an increased risk in the diabetic population, the systematic reviews report significant heterogenicity and come short in explaining causality.…”
Section: Pathophysiologic Changes Of Diabetic Retinopathy and Glaucommentioning
confidence: 99%
“…4 Patients with diabetes are also at risk of developing cataract, uveitis, and glaucoma. [5][6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%